Development of a test bench to solve a simple labyrinth - Kapitány, Pálma; Szabó, Máté (Design of Machines and Structures, 2023)
This paper deals with building an automatic test bench for detecting and solving a simple maze. There are many suitable sensors for detecting walls and ball, as find quick and stabile algorithm for deliver the ball to the target. Two servo motor are used to tilt the table of the maze. The first part of the paper shows the experiences of using OV7076 camera with Arduino Nano which was used for the first time to solve the problem. The final version of the maze solver contains a USB camera, an Arduino UNO platform, OpenCV and PyCharm software. Furthermore, paper reveals possibilities of decision-making-process and the direction of following research work.